Dysregulation of CircRNA_0001946 Contributes to the Proliferation and Metastasis of Colorectal Cancer Cells by Targeting MicroRNA-135a-5p - Deng, Zhenwei; Li, Xiyao; Wang, Huaiming; Geng, Yongyong; Cai, Yongchang; Tang, Yuxin; Wang, Yijun; Yu, Xueqiao; Li, Libo; Li, Ruiping (Frontiers in Genetics, 2020)
This study was aimed to evaluate the potential function of circ-0001946 in the progression of colorectal cancer (CRC) and the related regulatory mechanism. First, the expression levels of circRNA_0001946 and microRNA-135a-5p (miR-135a-5p) in normal and CRC tissues were measured by quantitative real-time polymerase chain reaction (RT-qPCR). In addition, cell proliferation was assessed by the Cell Counting Kit-8 (CCK-8) assay, cell migration and invasion were evaluated by Transwell assays, and the cell cycle patterns were determined by flow cytometry. The relationship between the expression levels of circ_0001946 and miR-135a-5p was determined by dual-luciferase reporter assays. Our data showed that the expression of circ_0001946 was upregulated in CRC tissues, which was negatively correlated with tumor size, histologic grade, lymphatic metastasis, and TMN stage, and patients with circ_0001946 overexpression were more likely to have a poor prognosis. In addition, in vitro experiments showed that silencing circ_0001946 inhibited the epithelial–mesenchymal transition (EMT) pathway and markedly suppressed CRC cell growth, migration, and invasion. Furthermore, we discovered that the transfection of miR-135a-5p mimics could reverse the antitumor effects of circRNA_0001946 downregulation. To summarize, this study revealed that circRNA_0001946 might act as a tumor promoter by activating the miR-135a-5p/EMT axis and may be a promising treatment target for CRC.